Strategy to Increase the Competence of Employees of The National and Political Unity Agency of West Java Province - Firdausijah, Taqwaty; Muliawaty, Lia (ann4publisher@gmail.com, 2023)
Human resource competence is one of the factors that significantly influence an organization, where the competence of its human resources determines the success of an organization in achieving goals. The competence of employees of the National and Political Unity Agency of West Java Province still needs to improve. The study aims to examine and analyze employee competencies and strategies for improving employee competencies. The method used in this study is descriptive analysis with a quantitative approach. The strategy to improve the competence of employees of the National and Political Unity Agency of West Java Province is carried out by applying competencies with the characteristics of motives, traits, self-concept, knowledge, and skills with data analysis techniques using SWOT analysis. The results of research and discussion show that the competence of employees of the National and Political Unity Agency of West Java Province has remained the same due to the competence of motives, traits, and self-concepts still needing to be improved, knowledge and skills competence low. Based on the SWOT analysis results, a diversification strategy was obtained to improve the competence of employees of the National and Political Unity Agency of West Java Province. The diversification strategy, namely increasing the competence of employees of the National and Political Unity Agency of West Java Province, is carried out by utilizing the power to control threats and take advantage of existing opportunities.